Regarding clarification of GRC sunshade and curtain wall system confusion - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record consists of general correspondence regarding clarification of GRC sunshade and curtain wall system for BRACU new campus project.